N‐acetyl‐b‐D‐glucosaminidase: A potential cardiorenal biomarker with a relevant impact on ICD shock therapies and mortality. Issue 12 (6th September 2020) - Allgaier, Raphael; Strack, Christina; Wallner, Stefan; Hubauer, Ute; Uecer, Ekrem; Lehn, Petra; Keyser, Andreas; Luchner, Andreas; Maier, Lars; Jungbauer, Carsten
Abstract: Aims: Chronic heart failure may lead to chronic kidney disease. Previous studies suggest tubular markers N‐acetyl‐b‐D‐glucosaminidase (NAG) and Kidney‐injury‐molecule‐1 (KIM‐1) as potential markers for the cardiorenal syndrome (CRS). The prognostic value of NAG and KIM‐1 regarding implantable cardioverter defibrillator (ICD) shock therapies is unknown. Methods: We included 314 patients with an ICD and collected plasma and urine samples. Urine‐values of NAG and KIM‐1 got related to urinary creatinine. Outcomes of interest were sustained adequate shock therapies and a combined endpoint of all‐cause mortality, rehospitalisation due to congestive heart failure and adequate shock therapies. Follow up time was 32 months (IQR 6‐35 months). Results: KIM‐1 and NAG were positively correlated with NT‐proBNP (KIM‐1: r = .34, P  < .001; NAG: r = .47, P  < .001). NAG was significantly elevated in patients with primary prevention compared with secondary prevention ICD indication ( P = .003). According to Kaplan Meier analysis, NAG as well as NT‐proBNP were significant predictors for adequate ICD shock therapies and for the combined endpoint (each P  < .001). Elevated KIM‐1 showed no significant differences (each P = n.s.). In multivariate cox regression analysis, NAG as well as NT‐proBNP were both independent predictors for adequate ICD shock therapies as well as the combined endpoint, beside ejection fraction <35% (each P  < .05). Diabetes, primary prevention ICD indication, coronary artery disease, eGFR and age were no significant predictors for both endpoints (each P = n.s.). Conclusion: Similar to NT‐proBNP, NAG showed promising value for overall prognostication in ICD patients. Especially, NAG seems to incorporate an additional prognostic value regarding occurrence of ICD shock therapies. SUMMARY AT A GLANCE: Among 314 patients with ICD, NAG levels were significantly associated with clinically important outcomes including sustained adequate shock therapies and a combined endpoint of all‐cause mortality or rehospitalization. These findings suggest a possible link between kidney tubular injury and ventricular arrhythmias.